Estimating the cost-effectiveness of treatment for prevention of thromboembolic events in at-risk adults with non-valvular atrial fibrillation - Bellone, Marco; Pradelli, Lorenzo; Bo, Mario (Farmeconomia. Health economics and therapeutic pathways, 2018)
INTRODUCTION: The direct oral anticoagulants (DOACs) have demonstrated a more predictable effect and a more favorable risk-benefit ratio compared to the standard oral anticoagulant treatment for the prevention of stroke in patients with non-valvular atrial fibrillation (NVAF). AIM: To estimate the efficiency of DOACs (apixaban, dabigatran, edoxaban, and rivaroxaban vs. warfarin), in the prevention of clinical events in adult patients with NVAF. METHODS: A deterministic incremental cost-effectiveness analysis was performed to evaluate the avoidance of a clinical event and the incremental cost per avoided clinical event, in a hypothetical population of 100,000 adult patients with NVAF, over 1-year period. In the absence of head-to-head comparison trials between DOACs, relative risks were derived from a network meta-analysis. Clinical events considered include stroke/systemic embolism (SE) and major bleeding. Only direct health costs related to the management of clinical events and drug acquisition costs were considered. Clinical event management costs were derived from literature and from the Diagnosis Related Group (DRG) tariffs. Net annual treatment costs were calculated based on the daily dose reported in the Summary of Product Characteristics (SPCs) and the ex-factory price of each drug. RESULTS: Among DOACs, apixaban was associated with the highest net clinical benefit with 1,064 avoided events over 1 year, compared to warfarin (728 major bleeding events and 336 strokes/SE). Furthermore, apixaban is the most efficient DOAC, with a cost per avoided event equal to € 16,672 vs. warfarin (€ 24,120 for edoxaban 60 mg, € 36,777 for dabigatran 150 mg). CONCLUSION: Apixaban has the highest potential net clinical benefit among DOACs for patients with NVAF and the least incremental cost per avoided event for the Italian National Health Service.